Thermodynamic and surface properties of Al-Cu-Fe-Si-Ti liquid alloy - Dahal, Nilkantha; Mehta, Upendra; Gohivar, Ramesh Kumar; Koirala, Ram Prasad; Yadav, Shashit (BIBECHANA, 2025)
The thermodynamic and surface properties of the Al-Cu-Fe-Si-Ti liquid alloy were systematically investigated using theoretical models. These properties were investigated at different cross-sections from Fe and Ti corners. For the comparative study, the excess Gibbs free energy of mixing for the liquid alloy was determined using the Muggianu, Kohler, and Chou models, based on the thermodynamic database of constituent binary subsystems available in the literature. The activity of the system was calculated using Chou model. The activities of Al, Fe, Si, and Ti showed negative deviations from Raoult’s law, confirming strong complex-forming tendencies, whereas Cu exhibited positive deviations, highlighting its weaker interaction and tendency toward segregation. These deviations diminished with increasing temperature, indicating that elevated thermal energy reduces ordering interactions and promotes random mixing. The surface tension of the alloy was calculated using Butler equation using the thermodynamic database. Present investigations revealed that compositions enriched with elements of intrinsically higher surface tension exhibited larger overall surface tension values. Surface segregation studies demonstrated that Al possesses the strongest surface affinity, followed by Si, while Ti is the least surface-active element. These findings provide crucial insights into the thermodynamic stability and interfacial behavior of multicomponent Al–Cu–Fe–Si–Ti liquid alloys, which are essential for optimizing their processing and applications.